The contrasting interaction effects of improvisational behavior with entrepreneurial self-efficacy on new venture performance and entrepreneur work satisfaction - Hmieleski, Keith M.; Corbett, Andrew C. (Journal of Business Venturing, 2008)
Although improvisation is often considered to be an elemental component of entrepreneurship, little work has been done to evaluate factors that influence the relationship of entrepreneur improvisational behavior with important outcome variables. In an attempt to partly fill this gap, the current study examines the moderating effect of entrepreneurial self-efficacy on the relationship of founders' improvisational behavior with both the performance of their startups and their individual level of work satisfaction using a national (United States) random sample of 159 entrepreneurs. In alignment with our predictions, improvisational behavior was found to have a positive relationship with new venture performance (i.e., sales growth) when exhibited by founders who were high in entrepreneurial self-efficacy, whereas improvisational behavior was found to have a negative relationship with new venture performance when exhibited by founders who were low in entrepreneurial self-efficacy. Contrary to our expectations, entrepreneurial self-efficacy was found to have a negative moderating effect on the relationship between entrepreneur improvisational behavior and work satisfaction.